Review on Zakat Performance Studies using NVivo-12 - Nadia Nurul Izza (Islamic Social Finance, 2021)
The success of zakat is highly dependent on the institution or amil that manages it. Therefore, studies to see the performance and performance of zakat institutions are important. This study aims to identify and map studies related to the development of zakat performance research. The data analyzed consisted of 418 journals published from 1970-2022. Data is processed and analyzed using the Nvivo 12 Plus software application for coding automatically with a qualitative approach. The results show that there are at least 3 research lines related to the study of zakat performance, namely: Zakat efficiency, zakat social performance and zakat & management. In the future, it is certainly necessary to carry out more specific studies related to these topics, in the context of continuous improvement for zakat institutions.